2022
DOI: 10.1002/acn3.51707
|View full text |Cite
|
Sign up to set email alerts
|

A KCNC1‐related neurological disorder due to gain of Kv3.1 function

Abstract: Objective To further clarify genotype:phenotype correlations associated with variants in KCNC1 encoding the voltage‐gated potassium (K+) channel subunit Kv3.1 and which are an emerging cause of a spectrum of neurological disease including intellectual disability, isolated myoclonus, progressive myoclonus epilepsy, and developmental and epileptic encephalopathy. Methods We describe the clinical and genetic characteristics of a series of three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…6 More recently, three de novo heterozygous KCNC1 GoF variants (M430I, V432M, and V434L) were described in three patients with developmental delay and hypotonia, without epilepsy or myoclonus. 9 In the present study, we report a patient with DEE carrying a previously unreported de novo missense KCNC1 variant (V425M) characterized by an in vitro mixed functional pattern with prevalent GoF effects, and we show that fluoxetine counteracted the mutation-induced functional defects in vitro, resulting in a significant and longlasting clinical improvement when administered to the proband.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…6 More recently, three de novo heterozygous KCNC1 GoF variants (M430I, V432M, and V434L) were described in three patients with developmental delay and hypotonia, without epilepsy or myoclonus. 9 In the present study, we report a patient with DEE carrying a previously unreported de novo missense KCNC1 variant (V425M) characterized by an in vitro mixed functional pattern with prevalent GoF effects, and we show that fluoxetine counteracted the mutation-induced functional defects in vitro, resulting in a significant and longlasting clinical improvement when administered to the proband.…”
Section: Introductionmentioning
confidence: 57%
“…16 Kv3.1 channels are mainly expressed in fast-spiking inhibitory neurons, where they contribute to action potential repolarization without affecting the threshold for action potential generation, thereby allowing high-frequency firing. 1,17 Thus, we may speculate that the Kv3.1 V425M GoF variant, similarly to other GoF pore variants, 9 may hyperpolarize the resting membrane potential and hamper fast-spiking activity of these neurons in vivo, thus increasing the excitation/inhibition balance that triggers epileptic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenotypes include epilepsy in infancy with migrating focal seizures, progressive myoclonic epilepsy, epileptic encephalopathy, ataxia, and intellectual disability. 56 57 58 …”
Section: Discussionmentioning
confidence: 99%
“…Parvalbumin-positive fast-spiking GABAergic interneurons (PV-INs) specifically express Kv3.1 and Kv3.2 which determines the fast-spiking phenotype of these cells ( 6 9 ); recent work using cell type–specific proteomics in mice confirmed that Kcnc2 is among the most highly differentially expressed proteins in neocortical PV-INs ( 10 ). Variants in the Kv3 subfamily member gene KCNC1 cause a spectrum of neurologic disorders including developmental delay/intellectual disability, progressive myoclonus epilepsy, and early-onset developmental and epileptic encephalopathy (DEE) ( 11 15 ). Mice lacking Kv3.2 exhibit abnormal EEG patterns and increased susceptibility to PTZ-induced seizures, supporting the role of KCNC2 in human disease ( 7 ).…”
mentioning
confidence: 99%